SISTEM INFORMASI GRAFIK KEKERASAN TERHADAP PEREMPUAN DAN ANAK PADA BADAN PP,KB, & PA KABUPATEN BENER MERIAH BERBASIS WEB - Ira Zulfa; Richasanty Septima; Riana Shara Fathonah (STEKOM PRESS, 2021)
The information system for graphic violence at the PP, KB, & PA Agency in Bener Meriah Regency is currently still using a manual system. So that the graphic information on violence in the Bener Meriah Regency PP, KB & PA Agency is not efficient. The web which has advantages and qualities in data collection and data calculation is catching up. With this system, it is easier for officers to collect and calculate data on violence against women and children.